A Study on the Evidence for Octupole Correlations in 140,142CS: Studying Octupole Correlations in Cs Isotopes (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The present Paper, entitled “A Study On The evidence for octupole correlations in 140,142Cs”, Focuses On The Evidence for octupole correlation. For nuclei with a small number of valence particles (N 85), octupole effects were explained due to octupole phonon excitations. In nuclei with a larger number of valence particles, one expects stronger octupole correlations, which will eventually cause octupole deformations of the nuclear potential. At N is equal 85, the number of valence particles may not be large enough to cause an octupole instability of the nuclear mean field, yet sufficient for numerous octupole excitations to appear. To check the stability of octupole excitations in 140Cs, Nuclear shapes in these neutron-rich Cs isotopes are expected to change gradually from a spherical shape in 137,138,139Cs to a weak deformed shape in 140,141,142Cs and then to a well deformed shape in 143,144,145Cs. Octupole correlations were observed in 141Cs and 143Cs.